Application of nickel-cobalt alloy in the composite anode to enhance characteristics of tubular SOFCs - Ivanov, Aleksey Vitalievich; Chikishev, Stepan Andreevich; Bervitskaya, Olga S.; Ichetovkina, Victoria A.; Ichetovkin, Zakhar Nikolaevich; Fominykh, Alexander M.; Vorotnikov, Vladimir A.; Bobro, Mark S.; Kuzmin, Anton Valerievich (Электрохимическая энергетика)
The electrochemical characteristics of the tubular solid oxide fuel cells (SOFC) and the symmetrical anodic cells with conventional nickel-cermet and modified nickel-cobalt cermet anodes were studied using voltammetry, electrochemical impedance spectroscopy, and distribution of relaxation time analysis. The tubular SOFC with the modified anode exhibited higher power output and demonstrated lower power loss at reduced temperatures, which is attributed to higher electrical conductivity and lower activation energy of the anodic electrode reaction.